A new small deinonychosaur (Dinosauria: Theropoda) from the Late Cretaceous of Patagônia, Argentina - Porfiri,Juan D. (2011)
Here we report on a new small deinonychosaurian theropod, Pamparaptor micros gen. et sp. nov., from the Late Cretaceous of Patagônia, Argentina. Pamparaptor micros exhibits a pedal structure previously unknown among South Américan deinonychosaurians. The new material provides new evidence about the morphology and taxonomic diversity of Patagônian deinonychosaurs. Pamparaptor is the smaller non-avialae Patagônian deinonychosaur, probably with about 0.50-0.70 meters, long. The pedal construction resembles, that of Troodontid or basal Dromaeosaurids. Nevertheless, up to now, we considered Pamparaptor a peculiar Patagônian Dromaeosaurid with troodontid-like pes.